ENaC in the Rabbit Lacrimal Gland and its Changes During Sjögren Syndrome and Pregnancy. Issue 5 (September 2015) - Wang, Mingwu; Huang, Jianyan; Lu, Michael; Zhang, Shunhua; Ding, Chuanqing
Abstract : Purpose: Epithelial sodium channel (ENaC) plays a critical role in the control of Na + balance and the development and progression of exocrine gland pathologic condition. The aim of the present study was to investigate the presence of ENaC in the rabbit lacrimal gland (LG) and its potential changes during induced autoimmune dacryoadenitis (IAD) and pregnancy. Methods: Total messenger RNA (mRNA) of α, β, and γ subunits was extracted from whole LG, acinar cells, and ductal cells by laser capture microdissection (LCM) for real-time reverse-transcriptase polymerase chain reaction. Lacrimal glands were processed for Western blot and immunofluorescence. Results: Messenger RNA for both α and γ was expressed in whole LG lysates, whereas β was undetectable. In rabbits with IAD, the levels of mRNA for α and γ were 20.9% and 58.9% lower ( P <0.05), whereas no significant changes were observed in term-pregnant rabbits ( P =0.152). However, we were unable to detect mRNA of any subunit in LCM specimens of ductal cells because of their low levels. Western blot demonstrated bands for both α (90 kDa) and γ (85 kDa) but β was undetectable. In rabbits with IAD, densitometry analysis showed that expression of α decreased 22%, whereas γ decreased 26% ( P <0.05). In pregnant rabbits, however, α expression was 31% lower, whereas γ expression was 34% lower ( P <0.05). From immunofluorescence studies, all subunits were present in ductal cells, whereas virtually no immunoreactivity was detected in acini. No noticeable changes of their distribution pattern and intensity were found in rabbits with IAD or during pregnancy. Conclusions: The present study demonstrated the presence of ENaC in the rabbit LG and its alterations in IAD and pregnancy, suggesting that ENaC may contribute to the pathogenesis of altered LG secretion and ocular surface symptoms in these animals.